What drives job satisfaction among community pharmacists? An application of relative importance analysis - Olajide O. Fadare; Matthew J. Witry; Caroline A. Gaither; William R. Doucette; Jon C. Schommer (Elsevier, 2023)
Background: Pharmacy employers want to improve pharmacists' job satisfaction, but ratings of job satisfaction are highly subjective, as evaluating job satisfaction involves weighing simultaneously the importance of multiple correlated determinants that are often perceived unequally. Objectives: To 1) describe the application of relative importance analysis in estimating the predictive ability of correlated determinants of job satisfaction, and to rank the determinants in order of relative importance, and 2) explore how the perceived relative importance of job satisfaction predictors may vary across community pharmacists' age, gender, and work setting categories. Methods: Data were obtained from the 2019 National Pharmacy Workforce Survey administered to 96,110 licensed U.S. pharmacists. Multiple regression analysis (MR) and relative weight analysis (RWA) were used to assess the predictive ability of determinants to explain pharmacists' job satisfaction. Subgroup analyses were performed to explore variations in the perceived relative importance of predictors across pharmacists' age, gender and work setting categories. Results: Over the entire sample of community pharmacists, no personal experience of workplace discrimination [RW = 0.0613, rank = 1] and less reported engagement in advanced dispensing activities [RW = 0.0235, rank = 2] were most associated with greater job satisfaction, as both predictors jointly accounted for 67.5% of the predicted criterion variance (R2). Pharmacists' compensation was observed to have the lowest perceived relative importance for predicting job satisfaction [RW = 0.0005, rank = 6], accounting for 0.5% of R2. Between-group comparisons showed that, no personal experience of workplace discrimination had the highest perceived relative importance for job satisfaction across pharmacists' age groups, among women, and across most work settings except small chain pharmacies. Within-group comparisons showed that pharmacists' compensation was significantly more important than professional interactions (ΔRW(PC-PPI) 0.2900 [0.0637, 0.5360]) for job satisfaction among pharmacists in large chain pharmacies, while patient-care services was significantly more important than compensation for job satisfaction in independent (ΔRW(PPS-PC) 0.1761 [0.0017, 0.5980]) and health system retail pharmacists (ΔRW(PPS-PC) 0.4190 [0.0444, 0.8303]). Conclusions: Relative importance analysis corroborated multiple regression and provided a more interpretable presentation of variable influence on community pharmacists job satisfaction as the importance of personal and workplace characteristics in how pharmacists evaluate their job satisfaction varied across age, gender and work setting categories.